Hereditary Myokymia and Paroxysmal Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A family with autosomal dominant hereditary myokymia and paroxysmal ataxia, linked to chromosome 12p, is described from University Hospital Groningen, The Netherlands.